(untitled) (The Journal of Plant Protection Sciences, 2023)
Nematophagous fungi (NF) are the major antagonists of nematodes. They include nematode trapping fungi as well as endoparasitic fungi. For more than a century scientists are studying different facets of biology of NF including their potential as a bioagents to control nematodes. Their inconsistent success in control of nematodes in field tri als, however, is enigmatic. This paper takes a review of the researches done by various workers on the diversity, morphology ecology, physiology of nutrition, trap formation and mechanism of nematode capture as well as prob able causes of death. The review traces the shift in the areas of research as well as ups and downs in the interest shown by the researchers. Guide lines for organized, coordinated research to i) screen different strains of NF that are tolerant to antagonism by other fungi, and ii) develop a bioagent based on nematophagous fungi which will show consistent success for the controlling of phytonematodes are also suggested.